Faktor-Faktor Yang Mempengaruhi Voluntary Disclosure Dalam Laporan Tahunan Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2012-2014 - admin, YESI TRISNAWATI B11111063 (Jurnal Manajemen Update, 2016)
This research aims to analyze the firm characteristic factor that influencing voluntary disclosure in annual report. The firm characteristic that was applied in this research are liquidity (current ratio), leverage (debt to equity ratio), profitability (return on equity), and firm’s size (total assets). Quantitative method is used in this research. The population in this research consists of 144 manufacturing companies listed on Indonesia Stock Exchange in the periode 2012-2014. The sampling method using purposive sampling and obtained a sample of 67 companies. Data analyzed with test of classic assumption and examination of hypothesis with multiple linear regression method.Result of this research indicates that liquidity (current ratio), and firm’s size (total assets) significant effect to voluntary disclosure in annual report. Leverage (debt to equity ratio) and profitability (return on equity) had not a significant effect to voluntary disclosure in annual report.Keywords: Voluntary Disclosure, Idx